COMPOSITE SYNVOLCANIC INTRUSIONS ASSOCIATED WITH PRECAMBRIAN VMS-RELATED HYDROTHERMAL SYSTEMS - Galley A.G. (My University, 2003)
Large subvolcanic intrusions are recognized within most Precambrian VMS camps. Of these, 80% are quartz diorite-tonalite-trondhjemite composite intrusions. The VMS camps spatially associated with composite intrusions account for >90% of the aggregate sulfide tonnage of all the Precambrian, intrusion-related VMS camps. These low-alumina, low-K, and high-Na composite intrusions contain early phases of quartz diorite and tonalite, followed by more voluminous trondhjemite. They have a high proportion of high silica (>74% SiO2) trondhjemite which is compositionally similar to the VMS-hosting rhyolites within the volcanic host-rock successions. The quartz-diorite and possibly tonalite phases follow tholeiitic fractionation trends whereas the trondhjemites fall within the composition field for primitive crustal melts. These transitional M-I-type primitive intrusive suites are associated with extensional regimes within oceanic-arc environments. Subvolcanic composite intrusions related to the Archean Sturgeon Lake and Noranda, and Paleoproterozoic Snow Lake VMS camps range in volume from 300 to 1,000 km3. Three have a sill morphology with strike lengths between 15 and 22 km and an average thickness between 1,500 and 2,000 m. The fourth has a gross stock-like shape. The VMS deposits are principally restricted to the volcanic strata above the strike length of the intrusions, as are areally extensive, thin exhalite units. The composite intrusions contain numerous internal phases which are commonly clustered within certain parts of the composite intrusion. These clusters underlie eruptive centers surrounded by areas of hydrothermal alteration and which contain most of the VMS deposits. Early quartz-diorite and tonalite phases appear to have intruded in rapid succession. Evidence includes gradational contacts, magma mixing and disequilibrium textures. They appear to have been emplaced as sill-dike swarms. These early phases are present as pendants and xenoliths within later trondhjemite phases. The trondhjemite phases contain numerous internal contacts indicating emplacement as composite sills. Common structural features of the composite intrusions include early xenolith phases, abundant small comagmatic dikes, fractures and veins and, in places, columnar jointing. Internal phases may differ greatly in texture from fine- to coarse-grained, aphyric and granophyric through seriate to porphyritic. Mineralogical and isotopic evidence indicates that early phases of each composite intrusion are affected by pervasive to fracture-controlled high-temperature (350-450 °C) alteration reflecting seawater-rock interaction. Trondhjemite phases contain hydrothermal-magmatic alteration assemblages within miarolitic cavities, hydrothermal breccias and veins. This hydrothermal-magmatic alteration may, in part, be inherited from previously altered wall rocks. Two of the four intrusions are host to Cu-Mo-rich intrusive breccias and porphyry-type mineralization which formed as much as 14 Ma after the main subvolcanic magmatic activity. The recognition of these Precambrian, subvolcanic composite intrusions is important for greenfields VMS exploration, as they define the location of thermal corridors within extensional oceanic-arc regimes which have the greatest potential for significant VMS mineralization. The VMS mineralization may occur for 2,000 m above the intrusions. In some cases, VMS mineralization has been truncated or enveloped by late trondhjemite phases of the composite intrusions. Evidence that much of the trondhjemitic magmatism postdates the principal VMS activity is a critical factor when developing heat and fluid flow models for these subseafloor magmatic-hydrothermal systems.
Keywords: VMS DEPOSITS; SUBVOLCANIC; LOW-ALUMINA TONALITE-TRONDHJEMITE; EXTENSIONAL ENVIRONMENTS; LARGE-SCALE ALTERATION SYSTEMS; Proterozoic; Archean; Paleoproterozoic; Precambrian::Proterozoic; Докембрий::Протерозой; Докембрий::Архей; Precambrian::Archean; Докембрий::Протерозой::Палеопротерозойская; Precambrian::Proterozoic::Paleoproterozoic